The South and the New Deal - Biles, Roger, 1950- (Book collections on Project MUSE., 2006)
When Franklin D. Roosevelt was sworn in as president, the South was unmistakably the most disadvantaged part of the nation. The region's economy was the weakest, its educational level the lowest, its politics the most rigid, and its laws and social mores the most racially slanted. Moreover, the region was prostrate from the effects of the Great Depression. Roosevelt's New Deal effected significant changes on the southern landscape, challenging many traditions and laying the foundations for subsequent alterations in the southern way of life. At the same time, firmly entrenched values and institu.